The Effect of Chemo-Entrepreneurship-Based Chemistry Learning Integrated with Values Education on Eleventh-Grade Students’ Learning Outcomes and Motivation - Ningrum, Sutria; Suprihatiningrum, Jamil (Journal of Tropical Chemistry Research and Education, 2024)
Chemistry learning innovations must be continuously pursued to prepare students for Era Society 5.0 and overcome academic and non-academic problems, including juvenile delinquency. One of the chemistry learning innovations carried out by this study is the application of chemo-entrepreneurship-based chemistry learning integrated with Values Education (VE). This study aimed to offer evidence for developing student learning outcomes and motivation through integrating values education into chemo-entrepreneurship-based chemistry learning. A quasi-experimental study was conducted to determine the effect of chemo-entrepreneurship-based chemistry learning integrated with VE on learning outcomes (affective and cognitive domains) and the motivation of grade XI students at Senior Secondary School Ajisaka, Tulang Bawang, Lampung. The sample was selected using a saturated cluster random sampling technique to determine the control group (XI-1) and the experimental group (XI-2). Students learning outcomes on the affective domain and motivation were measured by the Mann-Whitney test while learning outcomes on the cognitive domain was measured by independent sample t-tests on pretests and posttests taken by students. The study demonstrated that students exhibited a statistically significant change in learning outcomes and motivation due to these treatments.